2017
DOI: 10.3390/land6020031
|View full text |Cite
|
Sign up to set email alerts
|

Rangelands: Where Anthromes Meet Their Limits

Abstract: Defining rangelands as anthromes enabled Ellis and Ramankutty (2008) to conclude that more than three-quarters of Earth's land is anthropogenic; without rangelands, this figure would have been less than half. They classified all lands grazed by domestic livestock as rangelands, provided that human population densities were low; similar areas without livestock were excluded and classified instead as 'wildlands'. This paper examines the empirical basis and conceptual assumptions of defining and categorizing rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Under these conditions, it is thought that changes in rangeland production are more driven by variations of rainfall than by stocking rates (von Wehrden et al 2012;Engler and von Wehrden 2018). Subsequent work has shown that the vast majority (72%) of the world's rangelands have CVs less than 33% (Sayre et al 2017). Therefore, one needs to be careful about the overall facile link between pastoralism and non-equilibrium ecology when considering pastoralism's environmental effects.…”
Section: Unexamined Relationshipsmentioning
confidence: 99%
“…Under these conditions, it is thought that changes in rangeland production are more driven by variations of rainfall than by stocking rates (von Wehrden et al 2012;Engler and von Wehrden 2018). Subsequent work has shown that the vast majority (72%) of the world's rangelands have CVs less than 33% (Sayre et al 2017). Therefore, one needs to be careful about the overall facile link between pastoralism and non-equilibrium ecology when considering pastoralism's environmental effects.…”
Section: Unexamined Relationshipsmentioning
confidence: 99%
“…These ranchers navigated this complexity by a moral consideration of care giving and responsibility in moments of uncertainty. Sayre et al (2017, p. 348) described rangelands as "lands that have not (yet) been converted to other uses with higher rates of economic production and return, and their extant ecological diversity persists precisely because they have not been altered by more intensive land uses, which typically result in simplification," but we documented intentions and practices of ecological care that have not (yet) been reshaped to intensive productivist framings among ranchers operating where "anthromes meet their limits" (Sayre et al 2017) in the Western Great Plains. Valuing this care work in dynamic, shifting social contexts under variable market and weather/ climate conditions on semi-arid rangeland systems may greatly enhance grassland biodiversity conservation efforts at a time when even small patches of habitat play a critical role conserving biodiversity (Wintle et al 2019).…”
Section: Resultsmentioning
confidence: 88%
“…Rangelands are also resilient to politics and policy, perhaps more so than previously recognized (Sayre et al 2017). Ranchers consider the influence of socio-cultural and economic relations on their rangeland resources, communities, and largely family-farm-businesses (Didier and Brunson 2004;Fulton et al 2011).…”
Section: Study Sitementioning
confidence: 99%
“…Extensive pastoralism is the most ecologically appropriate and sustainable use of drylands and grassy ecosystems (Veldman et al, 2015b;Behnke and Mortimore, 2016;Sayre et al, 2017). Pastoral land use in these ecosystems has adapted to this high highly variable and unpredictable resource base through mobility, opportunism and reciprocity, and the inherent resilience and adaptability of pastoralism make it likely to emerge as an increasingly important land use under climate change (Blench, 2001;Boone et al, 2018).…”
Section: Rangelands and Open Ecosystems: Undervalued And Neglectedmentioning
confidence: 99%
“…Rangelands and the pastoralists they support are similarly neglected in literature and policy. Global estimates of the extent and distribution of rangeland are highly variable due to the use of imprecise definitions (Phelps and Kaplan, 2017), and a tendency to map rangelands as a "residual category" of land that is not forest, cultivated or urban (Sayre et al, 2017). Data on agriculture, livestock and forestry are inadequate for informing policymaking on rangeland-based livestock systems (Johnsen et al, 2019).…”
Section: Rangelands and Open Ecosystems: Undervalued And Neglectedmentioning
confidence: 99%